THE REVITALIZATION OF ULTIMUM REMEDIUM IN THE REFORM OF INDONESIA’S CRIMINAL JUSTICE SYSTEM - Fajar Rachmad Dwi Miarsa; Hermawan Hermawan; Ophie Virginia; Nonaqu Beautyla Putri (PT. Altin Riset Publishing, 2026)
This study examines the revitalization of the principle of ultimum remedium in the reform of Indonesia’s criminal justice system, which reflects a paradigm shift from a retributive approach to restorative, corrective, and rehabilitative approaches, as embodied in Law No. 1 of 2023 on the National Criminal Code. The issue examined is the deviation in the application of the ultimum remedium principle, which in practice has shifted to primum remedium, resulting in criminal law often being used as the primary means of punishment. This situation fuels overcriminalization and increases the burden on correctional institutions. This study employs a normative legal method using legislative, conceptual, and historical approaches through qualitative analysis of primary and secondary legal sources. The results of the study indicate that although the National Criminal Code has strengthened alternative sentencing and restorative justice, the application of the principle of ultimum remedium remains hindered by the legal culture of law enforcement officials, the broad scope of discretion, and inconsistencies in law enforcement practices. Revitalizing the principle of ultimum remedium is necessary so that criminal law truly serves as a last resort in resolving cases, thereby creating a penal system that is proportional, humane, and oriented toward substantive justice and the protection of human rights.